EFFECTIVENESS OF THE DRUG "AKARAGOLD 72%" AGAINST COTTON SPIDER MITES - Hoshimov, Farhod; Bektemirov, Azizbek; Ergashev, Oybek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The article discusses the results of using a new insecticide «Akaragold 72%» em.k. to control spider mites on cotton crops. The drug «Akaragold 72%» em.k. manufactured by JV LLC "Ifoda Agro Kimyo Himoya" contains the active ingredients - propargite 66% and hexythiazox 6%.